Lutein content of selected local fruits and vegetables - Pasaporte, Melvin Santillan (2009)
Lutein was quantified in six selected locally available fruit and vegetables namely: horseradish tree (Moringa oleifera) locally called malunggay, Malabar spinach ( Basella alba L.) locally called alugbati, carrots (Daucus carota), calamansi(Citrofortunella microcarpa), bell pepper (Capsicum anuum), and bok choy (Brassica rapa L. subspecies chinensis). The analysis was done by RP-HPLC and the analyte was detected at 450mm using a UV/Vis Detector. The identity of the analyte was confirmed by its UV/Vis spectrum and Rf in thin layer chromatography. The green leafy vegetables contained by the highest amount of lutein: alugbati (81.6 bok choy (58.8 , and malunggay (55.7 while the non-green and non-leafy samples have the least amount of lutein: carrots (7.75 and calamansi rind (28.3 . only bell pepper did not show presence of lutein. The effect of boiling on the lutein content was tested and results showed that lutein was still present in the samples after boiling for 15 minutes. The green leafy vegetables still contained the highest amount of lutein: alugbati (137 , bok choy (71.1 and malunggay (171 , while non-green and non-leafy samples have the least amount: calamansi rind (46.8 and carrots (7.53 . Contrary to its nature of being heat sensitive, the natural environment in the cellular matrix may have protected lutein from thermal isomerization and other natural disintegration. It was also noted that there was an increase in the lutein content of the samples after the boiling process except in carrots. This may be attributed to the enhanced extractability and bioavailability of the analyte due to breakdown of the tissues after boiling s in the case of lycopene